Glycaemic control and its related factors among people with type 2 diabetes in low- and middle-income countries: a systematic review and meta-analysis - Siddiquea, Bodrun Naher; Magliano, Dianna J.; Chowdhury, Hasina Akhter; Chowdhury, Mohammad Rocky Khan; Afroz, Afsana; Shah, Sonali S.; Billah, Baki (Frontiers in Clinical Diabetes and Healthcare, 2025)
ObjectiveTo estimate the prevalence of inadequate glycaemic control and identify factors associated with it among people with type 2 diabetes mellitus (T2DM) living in low- and middle-income countries (LMICs).MethodsA systematic literature search was conducted in the Medline, Embase, CINAHL, PsychINFO, and Global Health databases for articles published between 1 January 2001 and 15 April 2025. Information was descriptively summarised following the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. The quality of the articles was assessed using the Newcastle-Ottawa Scale. Random effects model was used to obtain the pooled proportion of inadequate glycaemic control. Heterogeneity (I2) was tested, sensitivity analyses were performed, and publication bias was examined using Egger’s regression test.ResultsAmong 12,985 records, 62 studies from 28 countries involving 176,349 participants were reviewed. The estimated pooled proportion of inadequate glycaemic control (glycosylated haemoglobin [HbA1c] ≥7%) was 69% (95% confidence interval [CI]: 66%–72%, p <0.001, I2 = 99.10%), with no publication bias (Egger’s test, p = 0.489). A number of factors were associated with inadequate glycaemic control (overall p < 0.001), including education below secondary level (OR: 1.47, 95% CI: 0.98–1.97), rural residence (OR: 1.80, 95% CI: 1.33–2.28), obesity (OR: 1.17, 95% CI: 1.11–1.22), use of oral glucose-lowering drugs and/or insulin (OR: 4.06, 95% CI: 2.58–5.54 and OR: 2.44, 95% CI: 1.70–3.19, respectively), non-adherence to diet (OR: 2.13, 95% CI: 1.33–2.93) and treatment (OR: 2.08, 95% CI: 1.61–2.54), and physical inactivity (OR: 2.15, 95% CI: 1.35–2.95).ConclusionMore than two-thirds of people with T2DM in LMICs have inadequate glycaemic control. Urgent interventions are needed, focusing on sociodemographic, lifestyle, and treatment-related factors.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD: 42023390577.